Edible cups made from agar powder and seaweed / Nur Izzah Syafiqah Mohd Nor Adaha, Afiq Iskandar Yusri and Muhammad Faqin Mohd Yusof - Mohd Nor Adaha, Nur Izzah Syafiqah; Yusri, Afiq Iskandar; Mohd Yusof, Muhammad Faqin (2020)
Plastics are proved to be a big problem to human, environment and also marine life. One of the alternatives is to produce natural based polymer composites using biodegradable polymer which are extracted from seaweed and agar. Seaweed and agar have their own uniqueness which is low in cost, good degradation rate and environment friendly that can replace plastic as it can be consumed safely by animals especially the marine life, which in a way means that it gives back to the nature, thus will preserve the environment from the said disaster. We are familiar with plastic and glass cups for serving tea, coffee and chocolate, but we need a safer and environmental friendly option like edible cups. Since it is edible and biodegradable so no waste is generated. Our objectives for this project is to create a biodegradable cup using agar powder and seaweed and to examine the durability of agar powder cup and seaweed cup. For the method of this project, firstly we prepare the agar solution and the next process is the extraction of seaweed. Then we prepare the seaweed solution and lastly we observe the result.